The multifaceted roles of metabolic enzymes in the Paracoccidioides species complex - Marcos, Caroline M. [UNESP]; Oliveira, Haroldo C. de [UNESP]; Silva, Julhiany de F. da [UNESP]; Assato, Patrcia A. [UNESP]; Fusco-Almeida, Ana M. [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (Frontiers Research Foundation, 2014)
Paracoccidioides species are dimorphic fungi and are the etiologic agents of paracoccidioidomycosis, which is a serious disease that involves multiple organs. The many tissues colonized by this fungus suggest a variety of surface molecules involved in adhesion. A surprising finding is that most enzymes in the glycolytic pathway, tricarboxylic acid (TCA) cycle and glyoxylate cycle in Paracoccidioides spp. have adhesive properties that aid in interacting with the host extracellular matrix and thus act as 'moonlighting'proteins. Moonlighting proteins have multiple functions, which adds a dimension to cellular complexity and benefit cells in several ways. This phenomenon occurs in both eukaryotes and prokaryotes. For example, moonlighting proteins from the glycolytic pathway or TCA cycle can play a role in bacterial pathogenesis by either acting as proteins secreted in a conventional pathway and/or as cell surface components that facilitate adhesion or adherence. This review outlines the multifunctionality exhibited by many Paracoccidioides spp. enzymes, including aconitase, aldolase, glyceraldehyde-3-phosphate dehydrogenase, isocitratelyase, malatesynthase, triose phosphate isomerase, fumarase, and enolase. We discuss the roles that moonlighting activities play in the virulence characteristics of this fungus and several other human pathogens during their interactions with the host.
Keywords: Paracoccidioides spp.; Moonlighting proteins; Virulence; Glycolytic pathway and tricarboxylic acid cycle; Glyoxylate cycle; adhesins